Production delays, technology choice and cyclical cobweb dynamics - Roberto Dieci; Sarah Mignot; Frank H. Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2021)
We develop a cobweb model in which firms, facing a two-period production delay, have access to a flexible (costly) and an inflexible (cheap) production technology. Moreover, firms select between production technologies depending on theirevolutionary fitness, measured in terms of past realized profits. The dynamics of our cobweb model is driven by a four-dimensional nonlinear map. We analytically show that its unique steady state may become unstable due to a Neimark-Sacker bifurcation, a scenario that gives rise to cyclical price dynamics, as observed in actual commodity markets. Simulations furthermore reveal that our cobweb model may also produce chaotic motion.
Keywords: D24; E32; Q11; 330; Cobweb models; production technology; cyclical price dynamics; bounded rationality and learning; stability and bifurcation analysis; chaos